Shiny coated product and its manufacturing method
A glowing paint film using thin-shaped titanium acid with a basic group and polymer compound addresses the issues of water-resistant adhesion and color stability, offering a silky feel and stable sky blue effect.
Patent Information
- Application Number
- JP2021023290
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-02-17
AI Technical Summary
Glowing pigments with a thin texture provide a silky feeling but lack water-resistant adhesion, and blending colored pigments to achieve desired colors results in color fluctuation and degradation.
A glowing paint film with a thin-shaped titanium acid having a layered crystal structure, treated with a basic group or its salt, and a polymer compound, which is applied without colored pigments to achieve a silky feeling and excellent water-resistant adhesion, producing a pale blue (sky blue) effect through scattered light.
The solution provides a glowing paint with no particle feeling, excellent silky texture, and superior water-resistant adhesion, achieving a stable sky blue color without color pigment blending.
Smart Images

Figure 0007623155000006 
Figure 0007623155000007 
Figure 0007623155000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a glittering coated article having a glittering coating film containing a glittering pigment provided on the surface of a substrate, and a method for producing the glittering coated article. [Background technology]
[0002] Conventionally, glittering coatings in which glittering coating films containing glittering pigments are provided on the surface of a substrate have been widely used. Glittering pigments have a strong glittering feel and a particulate feel (a glossy feel that appears to sparkle), and are known as pigments that impart a pearl-like luster to coating films. As such glittering pigments, those in which a titanium oxide layer is provided on the surface of scaly materials such as mica, scaly alumina, and scaly glass flakes are known (see Patent Document 1). However, as designs with a more luxurious feel, designs that do not have a particulate feel and have a silky feel (a silky smooth shine) are required. As a glittering pigment that has such a silky feel, flaky titanic acid is known.
[0003] For example, Patent Document 2 below discloses flaky titanic acid obtained by treating a titanate having a layered crystal structure with an acid and then reacting it with an organic basic compound to swell or peel off the interlayers. The flaky titanic acid is said to have an average major axis of 5 μm to 30 μm and an average thickness of 0.5 nm to 300 nm. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2003-225610 A [Patent Document 2] JP 2006-257179 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, although the bright pigment made of flaky titanic acid of Patent Document 2 has a silky feel without a grainy feel, there is a problem in that the water-resistant adhesion of the coating film is insufficient.
[0006] On the other hand, when a coating film is to be given a silky feel and color, a method of blending color pigments is used, but there are problems such as the color tone varying depending on the dispersion degree of the color pigment, and the color of the coating film deteriorating due to discoloration of the color pigment.
[0007] The object of the present invention is to provide a glittering coated article which has no grainy feel, has an excellent silky feel, has excellent water-resistant adhesion, and exhibits a pale blue color (sky blue) due to scattered light even without the addition of a coloring pigment, and a method for producing said glittering coated article. [Means for solving the problem]
[0008] The present invention provides the following glossy coated article and a method for producing the glossy coated article.
[0009] Item 1: A glittering coated product comprising a substrate and a glittering coating film provided on the surface of the substrate, the glittering coating film containing a glittering pigment and a polymeric compound having a basic group or a salt thereof, the glittering pigment being flaky titanic acid having an average thickness of 20 nm or more and 60 nm or less.
[0010] Item 2 L of the substrate surface * c * L in the h color system * Item 2. The glossy coated article according to item 1, wherein the value is less than 40.
[0011] Item 3. The glossy coated article according to Item 1 or 2, wherein the flaky titanic acid is obtained by allowing a polymeric compound or a salt thereof having a basic group, in an amount of more than 0.1 equivalent and less than 0.5 equivalent relative to the exchangeable ion capacity of the titanic acid, to act on titanic acid having a layered crystal structure, thereby swelling and peeling the interlayers in the layered crystal structure.
[0012] Item 4. The glittering coated article according to any one of Items 1 to 3, wherein the polymer compound having a basic group or a salt thereof is an amino-modified silicone.
[0013] Item 5. The glittering coated article according to any one of Items 1 to 4, wherein the average major axis of the flaky titanic acid is 5 μm or more and 30 μm or less.
[0014] Item 6. The glittering coated article according to any one of Items 1 to 5, wherein the content of the glittering pigment in the glittering coating film is 1% by mass or more and 40% by mass or less in terms of pigment concentration (PWC).
[0015] Item 7. The glittering coating film according to any one of Items 1 to 6, further comprising a polysaccharide derivative, wherein the polysaccharide derivative is formed by substituting at least a portion of the hydrogen atoms in hydroxyl groups contained in the polysaccharide with organic groups.
[0016] Item 8. The glossy coated article according to item 7, wherein the organic group is at least one selected from the group consisting of an alkyl group having a substituent, an alkyl group having no substituent, an acyl group having a substituent, and an acyl group having no substituent.
[0017] Item 9. The glossy coated article according to item 7 or 8, wherein the polysaccharide is cellulose.
[0018] Item 10. The glittering coated article according to any one of Items 7 to 9, wherein a mass ratio of the glittering pigment to the polysaccharide derivative (glittering pigment / polysaccharide derivative) is 5 / 95 or more and 50 / 50 or less.
[0019] Item 11. The glittering coated article according to any one of Items 1 to 10, wherein the glittering coating film has a thickness of 10 μm or more and 150 μm or less.
[0020] Item 12. A method for producing a glittering coated article according to any one of items 1 to 11, comprising the steps of preparing a glittering pigment composition containing a glittering pigment, a polymeric compound having a basic group or a salt thereof, and a solvent, and applying the glittering pigment composition to a substrate to form a glittering coating film.
[0021] Item 13. The method for producing a glittering coated article according to Item 12, wherein the glittering pigment composition further contains a polysaccharide derivative. Effect of the Invention
[0022] According to the present invention, it is possible to provide a glossy coated article which is free of a grainy feel, has an excellent silky feel, has excellent water-resistant adhesion, and exhibits a pale blue color (sky blue) due to scattered light even without the addition of a coloring pigment, as well as a method for producing the glossy coated article. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a glittering coated article according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional photograph showing an example of a glittering coating film provided on a glittering coated article of the present invention. [Diagram 3] FIG. 3 is a schematic diagram for explaining an example of the mechanism of exfoliation in a titanate having a layered crystal structure. [Figure 4] FIG. 4 is a cross-sectional photograph showing an example of a void (space) formed in a glittering coating film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Hereinafter, an example of a preferred embodiment of the present invention will be described. However, the following embodiment is merely an example, and the present invention is not limited to the following embodiment.
[0025] [Glossy coating] 1 is a schematic cross-sectional view showing a glittering coated article according to one embodiment of the present invention. As shown in FIG. 1, the glittering coated article 1 includes a substrate 2 and a glittering coating film 3.
[0026] A glittering coating film 3 is provided on a surface 2a of a substrate 2. The glittering coating film 3 contains a glittering pigment and a polymeric compound having a basic group or a salt thereof. The glittering pigment is flaky titanic acid having an average thickness of 20 nm or more and 60 nm or less.
[0027] As the glossy coating material 1 of this embodiment has the above-mentioned configuration, it has no grainy feel and exhibits an excellent silky feel, has excellent water-resistant adhesion, and can exhibit a pale blue color (sky blue) due to scattered light without the addition of a coloring pigment.
[0028] Conventionally, photoluminescent pigments made from flaky titanic acid have had the problem of insufficient water-resistant adhesion when formed into a coating film due to the presence of many voids (air gaps) as shown in Figure 4. On the other hand, when a coloring pigment is blended into the coating film to give it a silky feel and color, there are problems such as the color varying depending on the dispersion degree of the coloring pigment, and the color of the coating film deteriorating due to discoloration of the coloring pigment.
[0029] In response to this, the present inventors have discovered that by setting the average thickness of the flaky titanic acid as the glittering pigment contained in the glittering coating film 3 to be 20 nm or more and 60 nm or less, it is possible to exhibit a pale blue (sky blue) color without blending in a coloring pigment. In this regard, it is believed that by setting the average thickness of the flaky titanic acid to about 1 / 10 of the visible light wavelength, the glittering coating film 3 is made to appear pale blue (sky blue) by Rayleigh scattering.
[0030] The present inventors have also discovered that water-resistant adhesion can be improved by forming the glossy coating film 3 to contain, in addition to the above-mentioned glossy pigment, a polymeric compound having a basic group or a salt thereof.
[0031] In particular, when a polymeric compound having a basic group or its salt is used, the flaky titanic acid can be neatly oriented in the coating film, as shown in Figure 2, thereby further improving the silky feel and water-resistant adhesion.
[0032] Therefore, the glossy coating material 1 of this embodiment has no grainy feel, exhibits an excellent silky feel, has excellent water-resistant adhesion, and can exhibit a pale blue color (sky blue) due to scattered light without the addition of a coloring pigment.
[0033] Such a glittering coated article 1 can be suitably used in automobiles, household electrical appliances, office automation equipment, and the like.
[0034] In the above embodiment, the glittering coating film 3 is provided only on one surface 2a of the substrate 2, but the glittering coating film 3 may be provided on both surfaces 2a, 2b of the substrate 2.
[0035] Hereinafter, each member of the glittering coated article of the present invention, such as the glittering coated article 1, will be described in detail.
[0036] (base material) Examples of the material of the substrate include metal materials such as steel, aluminum, brass, copper, stainless steel, tinplate, zinc-plated steel, and alloyed zinc (Zn-Al, Zn-Ni, Zn-Fe, etc.) plated steel; polyolefin resins such as polyethylene and polypropylene; thermoplastic polyester resins such as polyethylene terephthalate resin, polybutylene terephthalate (PBT) resin, polycarbonate (PC) resin, and polycarbonate-polybutylene terephthalate (PC / PBT) resin; styrene resins such as acrylonitrile-styrene resin, acrylonitrile-butadiene-styrene (ABS) resin, and acrylonitrile-styrene-acrylate (ASA) resin; polymethyl methacrylate resin, acrylic resin, vinylidene chloride, polyamide resin, polyphenylene ether resin, polyoxymethylene resin, polyurethane resin, epoxy resin, and the like, or hybrid resins thereof and fiber-reinforced plastics (Fiber-Reinforced Plastics). Examples of suitable substrates include plastic materials (synthetic resin molded products) such as plastics and engineering resins; inorganic materials such as glass cement and concrete; wood; and fiber materials (paper, cloth, etc.). Depending on the material, these can be degreased or surface-treated as appropriate to prepare substrates. Furthermore, the above-mentioned substrates can also be coated with an undercoat or intermediate coat.
[0037] The undercoat coating film is formed to conceal the surface of a material and to impart anticorrosive and antirust properties to the material, and can be obtained by applying an undercoat paint, drying and curing it. The undercoat paint is not particularly limited, and examples thereof include electrocoating paint and solvent-based primer.
[0038] The intermediate coating film is formed to conceal the surface of the material or the undercoat coating film, and to impart adhesion, chipping resistance, etc., and can be obtained by applying an intermediate coating paint onto the surface of the material or the undercoat coating film, and then drying and curing the intermediate coating paint. The intermediate coating paint is not particularly limited, and for example, an organic solvent-based or water-based intermediate coating paint containing a thermosetting resin composition and a coloring material (pigment, dye, etc.) can be preferably used.
[0039] L of the substrate surface * c * L in the h color system * The value is preferably less than 40, more preferably 30 or less, and even more preferably 20 or less. * When the L value is less than the upper limit or equal to or less than the upper limit, transmitted light can be absorbed more, and the pale blue color exhibited by scattered light can be made more prominent. * The lower limit of the value is not particularly limited, and can be set to 1, for example.
[0040] L of the substrate surface * From the viewpoint of further reducing the value, the substrate is preferably a black substrate, although the substrate may be a white substrate and the color of the substrate is not particularly limited.
[0041] (Glitter coating film) The glittering coating film contains a glittering pigment and a polymeric compound having a basic group or a salt thereof. The glittering coating film may further contain a polysaccharide derivative. In this case, the water-resistant adhesion can be further improved.
[0042] The thickness of the glittering coating film is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, and preferably 150 μm or less, more preferably 100 μm or less, and even more preferably 50 μm or less. When the thickness of the glittering coating film is within the above range, there is no grainy feeling, and a more excellent silky feeling is exhibited, and the pale blue color (sky blue) exhibited by scattered light can be made more prominent.
[0043] Photoluminescent pigments; Flaky titanic acid as a luster pigment can be obtained, for example, by reacting titanic acid having a layered crystal structure with a polymeric compound or a salt thereof having a basic group in an amount greater than 0.1 equivalent and less than 0.5 equivalent relative to the exchangeable ion capacity of the titanic acid, thereby swelling and peeling off the spaces between the layers in the layered crystal structure.
[0044] Titanic acid having a layered crystal structure (hereinafter referred to as layered titanic acid) can be obtained, for example, by treating a titanate having a layered crystal structure (hereinafter referred to as layered titanate) with an acid and replacing the exchangeable metal cations with hydrogen ions or hydronium ions.
[0045] The acid used in the acid treatment is not particularly limited, and may be a mineral acid such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, or an organic acid. The type of layered titanic acid, the type and concentration of the acid, and the slurry concentration of the layered titanic acid affect the exchange rate of metal cations. In general, the lower the acid concentration and the higher the slurry concentration, the more the amount of remaining interlayer metal cations will be, making it difficult to peel off between layers, and therefore the average thickness of the peeled flaky titanic acid will be larger.
[0046] If the metal cations are difficult to remove, the acid treatment may be repeated as necessary.
[0047] The raw material layered titanate is, for example, Cs obtained by mixing cesium carbonate and titanium dioxide in a molar ratio of 1:5.3 and firing at 800°C according to the method disclosed in Japanese Patent No. 2979132. 0.7 Ti 1.83 O 4 Examples include:
[0048] In addition, potassium carbonate, lithium carbonate, and titanium dioxide were mixed in a molar ratio of K / Li / Ti=3 / 1 / 6.5, ground, and calcined at 800° C. according to the method disclosed in International Publication WO 99 / 11574. 0.8 L 0.27 Ti 1.73 O 4 Examples include:
[0049] In addition, according to the method disclosed in Japanese Patent No. 3062497, a compound of general formula A was obtained by using an alkali metal or an alkali metal halide or sulfate as a flux, mixing the mixture so that the flux / raw material mass ratio was 0.1 to 2.0, and firing the mixture at 700°C to 1200°C. X M Y □ Z Ti2-(Y+Z) O 4 [In the formula, A and M represent metals with different valences of 1 to 3, and □ represents a defective site of Ti. X is a positive real number satisfying 0 < X < 1.0, and Y and Z are 0 or positive real numbers satisfying 0 < Y + Z < 1.] Examples include layered titanates represented by the formula.
[0050] In the above general formula, A is a metal with a valence of 1 to 3, preferably at least one selected from the group consisting of K, Rb, and Cs. M is a metal with a valence of 1 to 3 different from metal A, preferably at least one selected from the group consisting of Li, Mg, Zn, Cu, Fe, Al, Ga, Mn, and Ni.
[0051] Specific examples include K 0.80 Li 0.27 Ti 1.73 O 4 、Rb 0.75 Ti 1.75 Li 0.25 O 4 、Cs 0.70 Li 0.23 Ti 1.77 O 4 、Cs 0.70 □ 0.18 Ti 1.83 O 4 、Cs 0.70 Mg 0.35 Ti 1.65 O 4 、K 0.8 Mg 0.4 Ti 1.6 O 4 、K 0.8 Ni 0.4 Ti 1.6 O 4 、K 0.8 Zn 0.4 Ti 1.6 O 4 、K 0.8 Cu 0.4 Ti 1.6 O 4 、K 0.8 Fe 0.8 Ti 1.2 O 4 、K 0.8 Mn 0.8 Ti1.2 O 4 , K 0.76 Li 0.22 Mg 0.05 Ti 1.73 O 4 , K 0.67 Li 0.2 Al 0.07 Ti 1.73 O 4 etc.
[0052] In addition, according to the method disclosed in International Publication No. 03 / 037797, 0.8 L 0.27 Ti 1.73 O 4 After pickling, the K obtained by calcination 0.5~0.7 L 0.27 Ti 1.73 O 3.85~3.95 may be also possible.
[0053] Flaky titanic acid can be obtained by treating a layered titanate with an acid to obtain layered titanic acid, and then reacting it with a polymeric compound or its salt having a basic group in an amount greater than 0.1 equivalent and less than 0.5 equivalent to the exchangeable ion capacity of the layered titanic acid to swell and peel off the interlayers in the layered crystal structure.
[0054] The average major axis of the flaky titanic acid is preferably 5 μm or more, more preferably 10 μm or more, preferably 30 μm or less, and even more preferably 25 μm or less. When the average major axis of the flaky titanic acid is equal to or more than the lower limit, the silky feeling can be further improved. On the other hand, when the average major axis of the flaky titanic acid is equal to or less than the upper limit, the flaky titanic acid can be dispersed more uniformly and parallelly in the coating film.
[0055] The average major axis of flaky titanic acid refers to the particle size in the plane direction perpendicular to the thickness direction of flaky titanic acid. The average major axis can be measured, for example, by observation with a transmission electron microscope (TEM) or a scanning electron microscope (SEM). Specifically, the average major axis can be measured by blending flaky titanic acid in a coating film and observing the cross section of the coating film with a TEM. The average major axis can be, for example, the average particle diameter of 100 flaky titanic acid particles measured in this way.
[0056] The average thickness of the flaky titanic acid is preferably 30 nm or more, more preferably 35 nm or more, and is preferably 55 nm or less, more preferably 50 nm or less. When the average thickness of the flaky titanic acid is within the above range, the pale blue color exhibited by scattered light can be made more prominent.
[0057] The average thickness of the flaky titanic acid can be measured by observation using a transmission electron microscope (TEM) and a scanning electron microscope (SEM). Specifically, the average thickness can be measured by blending the flaky titanic acid in a coating film and observing the cross section of the coating film using a TEM. The average thickness can be, for example, the average thickness of 100 flaky titanic acids measured in this manner.
[0058] The flaky titanic acid is preferably a single-layered titanic acid nanosheet in which the layered titanic acid is completely peeled off, but may be a laminate of 2 to 300 layers of titanic acid nanosheets. The laminate of titanic acid nanosheets is preferably a laminate of 10 to 300 layers of titanic acid nanosheets. In addition, a single-layered titanic acid nanosheet and a laminate of titanic acid nanosheets may be mixed. However, in this case, it is preferable that the flaky titanic acid is mixed so that the average thickness of the flaky titanic acid is within the above-mentioned range.
[0059] The content of the glittering pigment in the glittering coating film is preferably 1% by mass or more, more preferably 5% by mass or more, and preferably 40% by mass or less, more preferably 35% by mass or less, in terms of pigment concentration (PWC). When the content of the glittering pigment is within the above range, a more excellent silky feel can be obtained, and the pale blue color exhibited by scattered light can be made even more prominent.
[0060] A polymeric compound having a basic group or a salt thereof; The polymer compound or its salt having a basic group is not particularly limited as long as it is a polymer compound having an interlayer swelling effect of titanic acid having a layered crystal structure. The basic group is preferably a primary to tertiary amino group in view of availability of raw materials and ease of synthesis.
[0061] Examples of the polymeric compound having a basic group or its salt include (meth)acrylic polymers having a basic group, amino-modified silicone, etc., and preferably amino-modified silicone. In this specification, "(meth)acrylic" refers to "at least one of acrylic and methacrylic". The polymeric compound having a basic group or its salt may be used alone or in combination of two or more kinds.
[0062] Amino-modified silicone has a polysiloxane skeleton consisting of repeating (-Si-O-) units, and a part of the alkyl side chain of the silicon atom is modified with an amino-modified group. The amino-modified group may be bonded to a side chain of the silicone main chain, or may be bonded to an end. Examples of the amino-modified group include primary to tertiary amino groups and organic groups having primary to tertiary amino groups. Examples of the organic group having a primary to tertiary amino group include -R 1 -NH 2 (R 1 represents a divalent organic group.) Among these, a compound represented by the following formula (1) is preferred.
[0063] [ka]
[0064] (In formula (1), R 2 Ha-NH 2 or -R 1 -NH 2 Shows multiple R 2 may be the same or different, and n represents any integer. 1 represents a divalent organic group.
[0065] n is preferably an integer of 1 to 2,000.
[0066] R 1 Examples of the divalent organic group include an alkylene group and an arenediyl group.
[0067] The alkylene group is preferably an alkylene group having a carbon number of 1 to 10. Examples of such alkylene groups include a methylene group, an ethylene group, and a propylene group.
[0068] The arenediyl group is preferably an arenediyl group having a carbon number of 6 to 10. Examples of such arenediyl groups include a phenylene group.
[0069] The amino-modified silicone preferably has a kinetic viscosity of 10 mm at 25°C. 2 / s~2000mm 2 / s, more preferably 15mm 2 / s~600mm 2 / s, and more preferably 20 mm 2 / s~100mm 2 / s. The kinetic viscosity is 10mm 2 / s or less than 2000mm 2 If the viscosity is greater than 1 / s, it becomes difficult to disperse the polymer in an organic solvent. The kinetic viscosity can be measured using a kinetic viscosity measuring device.
[0070] The functional group equivalent (amino equivalent) of the amino-modified silicone is preferably 50 g / mol to 100,000 g / mol, more preferably 300 g / mol to 3,000 g / mol, and even more preferably 1,000 g / mol to 2,000 g / mol. By setting the functional group equivalent within the above range, the peeling degree can be further increased and the dispersion stability in an organic solvent can be further improved.
[0071] The amino-modified silicone is preferably water-insoluble, which means that the amount of the silicone that dissolves in 1 L of water at 25° C. is 10 g or less.
[0072] An example of the amino-modified silicone is a double-end amino-modified silicone represented by the following formula (2): R in formula (2) is a methylene group, a phenylene group, or the like.
[0073] [ka]
[0074] The amino-modified silicone may be used alone or in combination of two or more kinds.
[0075] The content of the polymer compound having a basic group or its salt is preferably 2% by mass or more, more preferably 5% by mass or more, even more preferably 8% by mass or more, preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 30% by mass or less, based on 100% by mass of the solid content of the glittering coating film (the glittering pigment composition constituting the glittering coating film). When the content of the polymer compound having a basic group or its salt is equal to or more than the lower limit, the water-resistant adhesion can be further improved. When the content of the polymer compound having a basic group or its salt is equal to or less than the upper limit, the silky feeling can be further improved.
[0076] In order to apply a polymer compound or a salt thereof having a basic group with an interlayer swelling effect, the polymer compound or a salt thereof having a basic group may be added directly, or a polymer compound or a salt thereof diluted with water or an aqueous medium, to a dispersion in which layered titanic acid after acid treatment or hot water treatment is dispersed in an aqueous medium under stirring.
[0077] The amount of the polymer compound having a basic group or its salt is preferably more than 0.1 equivalent and less than 0.5 equivalent of the polymer compound having a basic group or its salt with respect to the exchangeable ion capacity of the layered titanic acid, more preferably 0.2 equivalent or more and 0.4 equivalent or less. If the amount of the polymer compound having a basic group or its salt is 0.1 equivalent or less with respect to the exchangeable ion capacity of the layered titanic acid, delamination may not be expected. Also, if the amount of the polymer compound having a basic group or its salt is 0.5 equivalent or more with respect to the exchangeable ion capacity of the layered titanic acid, light blue (sky blue) coloring due to scattered light may not be expected.
[0078] The exchangeable ion capacity is the amount of exchangeable metal ions. For example, a layered titanate having the general formula A x M y □ z Ti 2-(y+z) O 4 where m is the valence of A and n is the valence of M, the equivalent weight refers to the value expressed as mx+ny. The equivalent weight refers to the amount of cationic groups generated by the reaction of a polymer compound having a basic group or a salt thereof with a hydrogen ion or hydronium ion present in layered titanic acid.
[0079] The average long diameter of the flaky titanic acid can be maintained at approximately the same level as that of the raw material layered titanate, unless strong shearing force is applied during the process of delaminating the layered titanate by reacting 0.5 equivalents or more of a polymeric compound having a basic group or its salt with the layered titanate.
[0080] In the present invention, the polymer compound having a basic group or a salt thereof is preferably not a low molecular weight amine having a molecular weight of 500 or less, and the glittering coating film preferably does not contain such a low molecular weight amine.
[0081] polysaccharide derivatives; The glittering coating film may further contain a polysaccharide derivative. In this case, the water-resistant adhesion can be further improved. This can be explained as follows.
[0082] When a hydrophobic amine 12 having a long hydrophobic portion as shown in FIG. 3 is used as a polymer compound having a basic group or its salt, the layered titanate 11 (titanate having a layered crystal structure) is swollen between layers and peeled off, while imparting hydrophobicity to the surface of the flaky titanic acid 13. However, when such a polymer compound having a basic group or its salt is used as a peeling agent, it tends to aggregate and become a rice cake-like aggregate after peeling in water. In contrast, by including a polysaccharide derivative 14, the dispersibility of the layered titanate 11 can be increased even in an organic solvent, and thus the water-resistant adhesion can be further increased like a binder.
[0083] The polysaccharide derivative has a polysaccharide skeleton as the main skeleton, and is constructed by substituting at least a portion of the hydrogen atoms of the hydroxyl groups contained in the polysaccharide with organic groups.
[0084] Examples of the organic group include an alkyl group having a substituent, an alkyl group having no substituent, an acyl group having a substituent, and an acyl group having no substituent. These organic groups may be used alone or in combination of two or more kinds.
[0085] The alkyl group preferably has a carbon number of 1 to 5. Examples of such an alkyl group include a methyl group, an ethyl group, etc. Examples of the substituent that the alkyl group has include a hydroxy group and a carboxy group.
[0086] The acyl group is preferably an acyl group having a carbon number of 2 to 5. Examples of such an acyl group include an acetyl group, a propionyl group, a butyryl group, and an isobutyl group.
[0087] Examples of polysaccharides include cellulose and starch. The polysaccharide is preferably cellulose. Cellulose is a linear polymer formed by polymerizing β-D-glucose molecules (β-D-glucopyranose) represented by the following formula (3) through β-1,4-glycosidic bonds. Each glucose unit constituting cellulose has three hydroxyl groups (m in the following formula (3) is a natural number).
[0088] [ka]
[0089] Polysaccharide derivatives are those in which the organic group is introduced into such cellulose by utilizing the hydroxy group. Cellulose is a main component of plants and can be obtained by separating and treating other components such as lignin from plants. In addition to those obtained in this way, cotton (e.g., cotton linters) and pulp (e.g., wood pulp) with a high cellulose content can be used either as is or after purification. The shape, size, and form of cellulose or its derivatives used as the raw material are preferably in the form of a powder with an appropriate particle size and shape in terms of reactivity, solid-liquid separation, and handleability.
[0090] The degree of polymerization of cellulose, expressed as the glucose polymerization degree (average polymerization degree), is preferably in the range of 50 to 5000. If the degree of polymerization is too low, the dispersion of the luster pigment may be insufficient. Conversely, if the degree of polymerization is too high, the compatibility with organic solvents may be impaired.
[0091] The average number of the above organic groups introduced per glucose unit of cellulose (DS LO) (organic group introduction ratio), i.e., the average number of hydroxy groups substituted with the above organic groups per glucose unit (hydroxyl group substitution degree), can be set appropriately depending on the physical properties required for the target bright pigment composition and the efficiency during production, and can be set, for example, in the range of 0.1 to 2.9, preferably 1.8 to 2.8, and more preferably 2.3 to 2.7.
[0092] Examples of the polysaccharide derivatives include cellulose esters and cellulose ethers.
[0093] Specific examples of cellulose esters include cellulose acetates such as cellulose diacetate (DAC) and cellulose triacetate (TAC); cellulose C such as cellulose propionate and cellulose butyrate; 3-5 Acetate; cellulose acetate such as cellulose acetate propionate (CAP) and cellulose acetate butyrate (CAB) 3-5 and cellulose acylate such as cellulose acylate.
[0094] Examples of the cellulose ethers include alkyl cellulose, hydroxyalkyl cellulose, hydroxyalkyl alkyl cellulose, carboxyalkyl cellulose, and alkyl-carboxyalkyl cellulose.
[0095] Examples of alkyl cellulose include C cellulose such as methyl cellulose and ethyl cellulose. 1-4 Alkyl cellulose and the like.
[0096] Examples of hydroxyalkyl cellulose include hydroxy C such as hydroxyethyl cellulose (HEC) and hydroxypropyl cellulose (HPC). 2-4 Alkyl cellulose and the like.
[0097] Hydroxyalkyl alkyl celluloses include, for example, hydroxy C alkyl celluloses such as hydroxypropyl methyl cellulose. 2-4 Alkyl C1-4 Alkyl cellulose and the like.
[0098] An example of the carboxyalkyl cellulose is carboxymethyl cellulose (CMC).
[0099] Examples of alkyl-carboxyalkyl cellulose include methyl carboxymethyl cellulose.
[0100] Among these, cellulose esters and cellulose ethers are preferred, and ethyl cellulose and cellulose acetate butyrate (CAB) are more preferred.
[0101] These polysaccharide derivatives may be used alone or in combination of two or more.
[0102] The content of the polysaccharide derivative is preferably 20% by mass or more, more preferably 30% by mass or more, even more preferably 45% by mass or more, preferably 95% by mass or less, more preferably 90% by mass or less, and even more preferably 85% by mass or less, based on 100% by mass of the solid content of the glittering coating film (the glittering pigment composition constituting the glittering coating film). When the content of the polysaccharide derivative is equal to or more than the lower limit, the water-resistant adhesion can be further improved. When the content of the polysaccharide derivative is equal to or less than the upper limit, the silky feeling can be further improved.
[0103] The mass ratio of the luster pigment to the polysaccharide derivative (luster pigment / polysaccharide derivative) is preferably 5 / 95 or more, more preferably 7 / 93 or more, even more preferably 9 / 91 or more, and preferably 50 / 50 or less, more preferably 40 / 60 or less, and even more preferably 35 / 65 or less. When the mass ratio (luster pigment / polysaccharide derivative) is equal to or more than the lower limit, the silky feeling can be further improved. When the mass ratio (luster pigment / polysaccharide derivative) is equal to or less than the upper limit, the water-resistant adhesion can be further improved.
[0104] Other additives; The glossy coating film may contain additives such as curing agents, binder resins, other glossy pigments excluding flaky titanic acid, colorants (pigments, dyes, etc.), extender pigments, anti-rust pigments, UV absorbers, light stabilizers, antioxidants, plasticizers, dispersants, leveling agents, surface conditioners, anti-sagging agents, thickeners, defoamers, lubricants, anti-settling agents, and rheology control agents, as appropriate, provided that the additives do not impair the design.
[0105] Examples of the curing agent include polyisocyanate compounds, amino resins, polycarboxylic acid compounds, etc., and are preferably at least one selected from polyisocyanate compounds and amino resins. By including a curing agent, the water-resistant adhesion of the glittering coating film can be further improved.
[0106] Examples of the polyisocyanate compound include aliphatic polyisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, dimer acid diisocyanate, and lysine diisocyanate; biuret type adducts, isocyanurate ring adducts, allophanate type adducts, and uretdione type adducts of these aliphatic polyisocyanates; alicyclic diisocyanates such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and methylcyclohexane-2,4- or -2,6-diisocyanate; biuret type adducts and isocyanurate ring adducts of these alicyclic diisocyanates; xylylene diisocyanate, tetramethylxylylene diisocyanate, tolylene Examples of such aromatic diisocyanate compounds include diisocyanates, 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate, and 1,4-naphthalene diisocyanate; biuret-type adducts and isocyanurate ring adducts of these aromatic diisocyanates; hydrogenated MDI and derivatives of hydrogenated MDI; urethane adducts obtained by reacting a polyisocyanate compound with a hydroxyl group of a polyol such as ethylene glycol, propylene glycol, 1,4-butylene glycol, dimethylolpropionic acid, polyalkylene glycol, trimethylolpropane, or hexanetriol in a ratio such that an excess of isocyanate groups is present; and biuret-type adducts and isocyanurate ring adducts of these urethane adducts.
[0107] The polyisocyanate compound may be blocked. The blocked polyisocyanate compound is a compound obtained by adding a blocking agent to the isocyanate group of the above polyisocyanate compound. The blocked polyisocyanate compound produced by the addition is stable at room temperature, but it is desirable that the blocking agent dissociates to regenerate a free isocyanate group when heated to the baking temperature of the coating film (usually about 80°C to about 200°C). Examples of blocking agents that satisfy such requirements include phenol-based, lactam-based, alcohol-based, ether-based, oxime-based, active methylene-based, mercaptan-based, acid amide-based, imide-based, amine-based, imidazole-based, and pyrazole-based blocking agents. Among these, in particular, blocked polyisocyanate compounds using active methylene-based or pyrazole-based blocking agents can be preferably used.
[0108] When a polyisocyanate compound is used, the content thereof is preferably within the range of 1 part by mass to 300 parts by mass per 100 parts by mass of the total solid content of the polysaccharide derivative.
[0109] Examples of the amino resin include methylolated amino resins obtained by reacting amino components such as melamine, urea, benzoguanamine, acetoguanamine, steroguanamine, spiroguanamine, and dicyandiamide with aldehydes. Examples of the aldehyde include formaldehyde, paraformaldehyde, acetaldehyde, and benzaldehyde. In addition, the methylolated amino resins etherified with a suitable alcohol can also be used. Examples of the alcohols used for etherification include methyl alcohol, ethyl alcohol, n-propyl alcohol, i-propyl alcohol, n-butyl alcohol, i-butyl alcohol, 2-ethylbutanol, and 2-ethylhexanol. As the amino resin, melamine resins are preferred, and among them, methylolated melamine resins in which at least a part of the methylol groups is alkyl-etherified can be preferably used.
[0110] When an amino resin is used, the content thereof is preferably within the range of 1 part by mass to 300 parts by mass per 100 parts by mass of the total solid content of the polysaccharide derivatives.
[0111] Examples of the binder resin include acrylic resin and polyester resin, and preferably acrylic resin.
[0112] The acrylic resin may be a homopolymer or copolymer obtained by radical polymerization of a radical polymerizable monomer mainly composed of an acrylic acid ester and / or a methacrylic acid ester. The polymer molecule preferably has a crosslinkable functional group such as a hydroxyl group or a carboxyl group.
[0113] Examples of acrylic acid esters and methacrylic acid esters include monoesters of acrylic acid or methacrylic acid with monovalent alcohols having 1 to 20 carbon atoms. Specific examples include methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, butyl acrylate, butyl methacrylate, hexyl acrylate, hexyl methacrylate, lauryl acrylate, and lauryl methacrylate.
[0114] Examples of the monomer containing the crosslinkable functional group include hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, hydroxypropyl methacrylate, caprolactone hydroxyethyl acrylate, caprolactone hydroxyethyl methacrylate, acrylic acid, methacrylic acid, maleic acid, fumaric acid, etc. In addition to the above, other monomers capable of radical copolymerization with the above monomers can be used, and for example, unsaturated compounds having one or more polymerizable double bonds in one molecule, such as acrylonitrile, methacrylonitrile, styrene, vinyl acetate, vinyl methyl ether, vinyl chloride, vinylidene chloride, ethylene, and propylene, can be used.
[0115] The acid value of the acrylic resin is preferably within the range of 3 mgKOH / g to 50 mgKOH / g. If the acid value is too low, the adhesion of the coating film may decrease, whereas if the acid value is too high, the water resistance may decrease.
[0116] The weight-average molecular weight (Mw) of the acrylic resin is preferably within the range of 200,000 to 1,000,000. If the weight-average molecular weight is too low, the effect of the present invention of stably maintaining the orientation of the glittering pigment in the coating film state before curing may not be fully obtained. If the number-average molecular weight is too high, the glittering pigment composition may have poor solubility in a solvent or may have too high a viscosity, resulting in poor handling. The weight-average molecular weight can be determined by gel permeation chromatography (GPC) using a styrene polymer as a standard. The ratio of the polysaccharide derivative to the binder resin is preferably within the range of polysaccharide derivative / binder resin=10 / 90 to 90 / 10 in terms of solid content mass ratio, more preferably 30 / 70 to 70 / 30, and even more preferably 40 / 60 to 60 / 40, from the viewpoint of further improving water-resistant adhesion, weather resistance, and the like.
[0117] Other examples of photoluminescent pigments include mica (artificial mica, synthetic mica, etc.), silica, alumina, and scaly particles such as glass flakes, and TiO 2 , SnO 2 , ZrO 2 , Fe 2 O 3 , ZnO 2 , Cr 2 O 3 , V 2 O 5 Examples of suitable pigments include flake-like particles having a multi-layer film made of a metal oxide such as aluminum oxide, titanium oxide, or the like; colored aluminum flake pigments; titanium metal flake pigments; stainless steel flake pigments; plate-like iron oxide pigments; and hologram pigments.
[0118] Examples of extender pigments include baryta powder, precipitated barium sulfate, barium carbonate, calcium carbonate, gypsum, clay, silica, white carbon, diatomaceous earth, talc, magnesium carbonate, alumina white, gloss white, and mica powder.
[0119] Examples of the rust-preventive pigment include aluminum dihydrogen tripolyphosphate and aluminum phosphomolybdate.
[0120] Examples of the ultraviolet absorbent include a benzotriazole-based absorbent, a triazine-based absorbent, a salicylic acid derivative-based absorbent, and a benzophenone-based absorbent.
[0121] [Method of manufacturing glittery coated products] The method for producing a glittering coated article of the present invention includes the steps of preparing a glittering pigment composition containing a glittering pigment, a polymeric compound having a basic group or a salt thereof, and a solvent, and applying the glittering pigment composition to a substrate to form a glittering coating film.
[0122] Specifically, the bright coated article of the present invention can be produced as follows.
[0123] First, a layered titanate is treated with an acid or hot water to obtain layered titanic acid, and then a polymeric compound or its salt having a basic group having an interlayer swelling effect is applied to the layered crystal structure to swell and peel the interlayers, thereby obtaining flaky titanic acid. The polymeric compound or its salt having a basic group is applied in an amount of more than 0.1 equivalent and less than 0.5 equivalent to the exchangeable ion capacity of the titanic acid.
[0124] Next, by adding flaky titanic acid to the solvent and stirring, a glittering pigment composition in which the flaky titanic acid is dispersed in the solvent can be obtained. When using a polysaccharide derivative, it is preferable to prepare a solution by adding the polysaccharide derivative to an organic solvent. By adding the flaky titanic acid to the obtained solution and stirring, a glittering pigment composition in which the flaky titanic acid is dispersed in the organic solvent can be obtained.
[0125] The solvent may be an organic solvent or may be water, and therefore the bright pigment composition may be a solvent-based paint or a water-based paint.
[0126] The organic solvent is not particularly limited, but examples thereof include aromatic hydrocarbons such as xylene, toluene, and ethylbenzene; aliphatic hydrocarbons such as hexane and heptane; esters such as ethyl acetate, n-butyl acetate, and isobutyl acetate; halogenated hydrocarbons such as carbon tetrachloride; alcohols such as methanol, ethanol, isopropanol, n-butanol, sec-butanol, and isobutanol; ethers such as n-butyl ether, dioxane, ethylene glycol monomethyl ether, and ethylene glycol monoethyl ether; and ketones such as methyl ethyl ketone, methyl isobutyl ketone, and diisobutyl ketone. Among these, the organic solvent is preferably an aromatic hydrocarbon or an ester. These organic solvents may be used alone or in combination.
[0127] The content of the organic solvent is not particularly limited and can be appropriately adjusted. For example, taking into consideration the viscosity suitable for application, it can be set to 60% by mass or more and 90% by mass or less in 100% by mass of the bright pigment composition.
[0128] Next, the obtained bright pigment composition is applied onto a substrate and dried to obtain the bright coated article of the present invention. The coating film constituting the bright coated article usually has a cured film thickness of preferably 1 μm to 200 μm, more preferably 10 μm or more and 150 μm or less, and even more preferably 20 μm or more and 50 μm or less.
[0129] During application, the solids concentration of the bright pigment composition is preferably 10% by mass or more and 40% by mass or less in order to obtain a more excellent silky feel.
[0130] The bright pigment composition can be applied by, for example, spin coating, spray coating, roller coating, dip coating, flow coating, knife coating, electrostatic coating, bar coating, die coating, brush coating, dripping, or the like.
[0131] The heating conditions in the method for forming a coating film of the bright pigment composition are not particularly limited, but the coating can be carried out, for example, by holding at 60° C. to 200° C. for 5 minutes to 30 minutes.
[0132] A topcoat layer may be provided on the obtained glossy coating film by applying a paint such as a clear paint. Examples of the clear paint include solvent-based paint, water-based paint, water-dispersed paint, and powder paint. The clear paint may be a colored clear paint. The components contained in the clear paint are not particularly limited, and a paint containing a film-forming thermosetting resin and a curing agent can be used.
[0133] Preferred examples of solvent-based clear coatings include combinations of acrylic resin and / or polyester resin with amino resin, or acrylic resin and / or polyester resin with a carboxylic acid-epoxy curing system, from the standpoint of transparency or acid etching resistance.
[0134] Examples of water-based clear paints include those containing resins that have been neutralized with a base to make the film-forming resins contained in the above-mentioned solvent-based clear paints water-based. This neutralization can be carried out by adding a tertiary amine such as dimethylaminoethanol or triethylamine before or after polymerization.
[0135] On the other hand, as the powder type clear paint, ordinary powder paints such as thermoplastic and thermosetting powder paints can be used. Thermosetting powder paints are preferred because they can provide a coating film with good physical properties. Specific examples of thermosetting powder paints include epoxy, acrylic and polyester powder clear paints, and acrylic powder clear paints with good weather resistance are particularly preferred.
[0136] The glossy coating film of the present invention formed on the surface of the substrate exhibits an excellent silky feel, and exhibits a pale blue (sky blue) color due to scattered light even without the addition of a coloring pigment, and has excellent water-resistant adhesion, so that it can be used, for example, for the outer panels of automobile bodies such as passenger cars, trucks, motorcycles, buses, etc.; automobile parts; and the outer panels of household electrical appliances such as refrigerators, washing machines, smartphones, and audio equipment, and is particularly suitable for use in the outer panels of automobile bodies and automobile parts. EXAMPLES
[0137] The present invention will be described in more detail below with reference to specific examples. The present invention is not limited to the following examples, and can be modified as appropriate within the scope of the present invention.
[0138] <Synthesis of flaky titanic acid> (Synthesis Examples 1 to 4) Titanium oxide (67.01 g), potassium carbonate (26.78 g), potassium chloride (12.04 g), and lithium hydroxide (5.08 g) were dry-ground and mixed to prepare a raw material, which was then calcined at 1,020°C for 4 hours. 7.9 kg of a 10.9% water slurry of the resulting powder was prepared, to which 470 g of a 10% aqueous sulfuric acid solution was added and stirred for 2 hours to adjust the pH of the slurry to 7.0. The product was separated, washed with water, dried at 110°C, and then calcined at 600°C for 12 hours. The resulting white powder was titanate K with a layered crystal structure. 0.6 Li 0.27 Ti 1.73 O 3.9 The average major axis was 15 μm.
[0139] 32.5 g of this titanate having a layered crystal structure was dispersed in 474.8 g of deionized water, and while stirring, 25.2 g of 95% sulfuric acid was added. After reacting at room temperature for 1 hour, the mixture was separated by suction filtration and washed with water. The same process was carried out again with the obtained solid matter. 2 The residual O content was 2.0%, and the metal ion exchange rate was 94%.
[0140] The total amount of the obtained layered titanic acid was added to deionized water so that the total weight was 2.5 kg, and while dispersing and stirring, both-end amino-modified silicone (manufactured by Shin-Etsu Silicone Co., Ltd.) was added in the amount shown in Table 1 below, and the mixture was stirred at room temperature for 1 hour. After that, the mixture was separated by suction filtration and washed with water to obtain flaky titanic acid.
[0141] [Table 1]
[0142] The amino-modified silicones A to B shown in Table 1 are as follows.
[0143] Amino-modified silicone A: Amino-modified silicone with both ends (Shin-Etsu Silicone, X-22-161A, side chain: methyl group, kinetic viscosity at 25°C: 25 mm 2 / s, functional group equivalent: 800g / mol) Amino-modified silicone B: Amino-modified silicone with both ends (Shin-Etsu Silicone, X-22-161B, side chain: methyl group, kinetic viscosity at 25°C: 55 mm 2 / s, functional group equivalent: 1500g / mol)
[0144] (Synthesis Example 5) The total amount of layered titanic acid obtained in the same manner as in Synthesis Examples 1 to 4 was added to deionized water so that the total weight of the mixture with the deionized water was 800 g. While dispersing and stirring, a solution of 17.3 g of dimethylethanolamine (1 equivalent relative to the layered titanic acid) dissolved in 182.8 g of deionized water was added, and the mixture was stirred at room temperature for 12 hours to obtain flaky titanic acid.
[0145] <Preparation of Glittering Pigment Composition and Glittering Coating Film> Example 1 The flaky titanic acid obtained in Synthesis Example 2 was mixed with a 10% by mass solution (solvent: xylene) of ethyl cellulose (hydroxyl group substitution degree: 2.54, organic group: ethyl group) using a defoaming conditioning mixer "Awatori Rentaro AR-250" (Thinky Corporation) for 10 minutes (rotation: 800 rpm, revolution: 2000 rpm) so that the PWC (pigment concentration) was 10% by mass, and then defoamed for 2 minutes (rotation: 60 rpm, revolution: 2200 rpm) to obtain a glittering pigment composition (flaky titanic acid-containing coating composition). The glittering pigment composition obtained did not show any sedimentation of solids even after standing for a long time, and had sufficient dispersion stability.
[0146] Next, the above-mentioned glittering pigment composition was applied twice to a hiding rate test paper (black undercoat) using a film applicator with a clearance of 200 μm. In this process, a glittering coating film was formed by drying at room temperature after each application, and a glittering coating was obtained. The thickness of the glittering coating film obtained was 30 μm. It was also confirmed that the glittering coating film obtained had flaky titanic acid with an average thickness of 40 nm and an average major axis of 15 μm uniformly and parallelly dispersed and oriented in the resin coating film in a very dense state. In the examples and comparative examples, the average major axis and average thickness of the flaky titanic acid were measured by observing the cross section of the coating film with a SEM (scanning electron microscope). As the SEM, Hitachi's product number "S-4000" was used. The average major axis was the average particle diameter of 100 flaky titanic acids measured, and the average thickness was the average thickness of 100 flaky titanic acids measured.
[0147] Example 2 A glittering pigment composition and a glittering coating film were prepared in the same manner as in Example 1, except that the flaky titanic acid obtained in Synthesis Example 2 was used so that the PWC was 20 mass %, and a glittering coated product was obtained. The thickness of the resulting glittering coating film was 32 μm.
[0148] Example 3 A glittering pigment composition and a glittering coating film were prepared in the same manner as in Example 1, except that the flaky titanic acid obtained in Synthesis Example 2 was used so that the PWC was 30 mass %, and a glittering coated product was obtained. The thickness of the resulting glittering coating film was 34 μm.
[0149] Example 4 A glittering pigment composition and a glittering coating film were prepared in the same manner as in Example 1, except that the flaky titanic acid obtained in Synthesis Example 4 was used so that the PWC was 10 mass %, and a glittering coated product was obtained. The thickness of the resulting glittering coating film was 29 μm.
[0150] Comparative Example 1 Except for using the flaky titanic acid obtained in Synthesis Example 1 so that the PWC was 10 mass %, a pigment composition and a coating film were prepared in the same manner as in Example 1, and a coated article was obtained. The thickness of the resulting coating film was 28 μm.
[0151] Comparative Example 2 A pigment composition and a coating film were prepared in the same manner as in Example 1, except that the flaky titanic acid obtained in Synthesis Example 3 was used so that the PWC was 10 mass %, and a coated article was obtained. The thickness of the resulting coating film was 31 μm.
[0152] Comparative Example 3 Except for using the flaky titanic acid obtained in Synthesis Example 5 so that the PWC was 10 mass % and mixing with a water-based urethane paint (urethane resin) instead of ethyl cellulose (hydroxyl group substitution degree: 2.54, organic group: ethyl group), a pigment composition and a coating film were prepared in the same manner as in Example 1, and a coated article was obtained. The thickness of the resulting coating film was 26 μm.
[0153] Comparative Example 4 Except for using a white background as the hiding power test paper, a pigment composition and a coating film were prepared and a coated product was obtained in the same manner as in Comparative Example 3. The thickness of the obtained coating film was 26 μm.
[0154] Comparative Example 5 A pigment composition and a coating film were prepared in the same manner as in Example 1, except that a conventional pearl pigment, titanium oxide-coated scaly alumina (product name "Xiralic T50-10", manufactured by Merck), was used in place of flaky titanic acid so as to have a PWC content of 10 mass %, and a coated product was obtained. The coating film obtained had a thickness of 35 μm.
[0155] Comparative Example 6 Except for using a white background as the hiding power test paper, a pigment composition and a coating film were prepared and a coated product was obtained in the same manner as in Comparative Example 5. The thickness of the obtained coating film was 35 μm.
[0156] <Evaluation of coating film> The design properties (grainy feel, silky feel, color measurement) of the coatings obtained in Examples 1 to 4 and Comparative Examples 1 to 6 were evaluated by the following test methods. In addition, the pigment compositions in Examples 1 to 4 and Comparative Examples 1 to 4 were applied to white painted panels in the same manner as in Example 1 to obtain glitter coatings, and the water-resistant adhesion was evaluated by the following test method.
[0157] [Particle feeling] The graininess of the coating film was visually evaluated according to the following criteria.
[0158] 〇: No graininess ×: Grainy texture
[0159] [Silky feel] The lightness (L) of the obtained coating (black background part of the hiding rate test paper) was measured at an incident angle of 45° and receiving angles of 15°, 25°, 45°, 75°, and 110° using a multi-angle spectrophotometer (MA68II, X-Rite). * The flop index (FI) value was calculated from the measured flop index value and evaluated. Note that a higher FI value indicates a more silky feel.
[0160] [Colorimetry] The chroma c of the obtained coating film was measured at incident angles of 45° and receiving angles of 15°, 25°, 45°, 75°, and 110° using a multi-angle spectrophotometer (MA68II, manufactured by X-Rite).* The chroma value and the hue angle h value were measured. * The higher the value, the more vivid the color is. The hue angle h=270° indicates the blue direction. * The values and h values (°) indicate the average values at acceptance angles of 15°, 25°, 45°, 75°, and 110°.
[0161] [Water-resistant adhesion (cross-cut test)] In accordance with "JIS K5400 General Test Methods for Paints," the glitter coating was immersed in 40°C warm water for 5 hours, and then a cross-cut tape peel test (2mm square, 100 grids) was performed to evaluate water-resistant adhesion.
[0162] <Paint film evaluation results> The results are shown in Table 2 below.
[0163] [Table 2]
[0164] As is clear from the evaluation results of the coating film, Examples 1 to 4 have no grainy feel compared to Comparative Examples 5 and 6, and Example 4 has a superior silky feel and has excellent design properties. In addition, in Examples 1 to 4, which were coated with a glittering pigment composition containing flaky titanic acid with an average thickness of 20 nm or more and 60 nm or less, * The value was high and the h value was close to 270°, which indicates that the color was blue. On the other hand, in Comparative Examples 1 and 2, which were coated with a pigment composition containing flaky titanic acid whose average thickness was not in the range of 20 nm or more and 60 nm or less, the c *From the low value, it can be seen that the blue color is not fully developed. This shows that by applying a glitter pigment composition containing flaky titanic acid having an average thickness of 20 nm or more and 60 nm or less to the surface of a substrate, a glitter coating film is obtained that is completely free of a grainy feel, has an excellent silky feel, and shows a pale blue (sky blue) color due to scattered light. In addition, it can be seen that Examples 1 to 4, which use a polymer compound having a basic group or a salt thereof, have excellent water-resistant adhesion compared to Comparative Examples 3 and 4, which use a low-molecular-weight amine. [Explanation of symbols]
[0165] 1...Glossy painted items 2...Base material 2a,2b…Surface 3…Glittering coating film 11...Layered titanate 12...Hydrophobic amine 13...Flake-like titanic acid 14...Polysaccharide derivative
Claims
1. A glittering coated article comprising a substrate and a glittering coating film provided on a surface of the substrate, The glittering coating film contains a glittering pigment, a polymer compound having a basic group or a salt thereof, and a polysaccharide derivative, The bright pigment is a flaky titanic acid having an average thickness of 20 nm or more and 60 nm or less, The polysaccharide derivative is formed by substituting at least a portion of the hydrogen atoms in hydroxyl groups contained in the polysaccharide with organic groups.
2. The L of the substrate surface * c * L in the h color system * The glossy coating according to claim 1 , wherein the value is less than 40.
3. The flaky titanic acid is a flaky titanic acid obtained by treating titanic acid having a layered crystal structure with a polymeric compound or its salt having a basic group in an amount greater than 0.1 equivalent and less than 0.5 equivalent relative to the exchangeable ion capacity of the titanic acid, thereby swelling and peeling the interlayers in the layered crystal structure.
4. The glittering coated article according to any one of claims 1 to 3, wherein the polymer compound having a basic group or a salt thereof is an amino-modified silicone.
5. The glittering coated article according to any one of claims 1 to 4, wherein the average long diameter of the flaky titanic acid is 5 µm or more and 30 µm or less.
6. The content of the glittering pigment in the glittering coating film is 1% by mass or more and 40% by mass or less in terms of pigment concentration (PWC), the glittering coated article according to any one of claims 1 to 5.
7. The glittering coating according to any one of claims 1 to 6, wherein the organic group is at least one selected from the group consisting of an alkyl group having a substituent, an alkyl group having no substituent, an acyl group having a substituent, and an acyl group having no substituent.
8. The glittering coating according to any one of claims 1 to 7, wherein the polysaccharide is cellulose.
9. The glossy coated article according to any one of claims 1 to 8, wherein the mass ratio of the glossy pigment to the polysaccharide derivative (glossy pigment / polysaccharide derivative) is 5 / 95 or more and 50 / 50 or less.
10. The glittering coating according to any one of claims 1 to 9, wherein the glittering coating has a thickness of 10 μm or more and 150 μm or less.
11. A method for producing a glittering coated article according to any one of claims 1 to 10, A step of preparing a bright pigment composition containing a bright pigment, a polymer compound having a basic group or a salt thereof, a polysaccharide derivative, and a solvent; and applying the above-mentioned glittering pigment composition to a substrate to form a glittering coating film.
Citation Information
Patent Citations
Method of forming luster color coating film
JP2003225610A
Aqueous medium dispersion of glitter pigment and glitter coating material
JP2006257179A
Method for producing surface-treated titanate pigment and surface-treated titanate pigment
JP2007153922A